The effect of home characteristics on dust antigen concentrations and loads in homes - Cho, Seung-Hyun (2006)
On-site home visits, consisting of a home inspection, dust sampling, and questionnaires were conducted in 777 homes belonging to an ongoing birth cohort study in Cincinnati, Ohio. Various home characteristics were investigated, and antigen levels (concentrations [μg/g] and loadings [μg/m(2)]; IU for cockroach allergen) in floor dust samples collected in child’s primary activity room were analyzed by ELISA. Monoclonal antibodies were used for the analysis of cat, house dust mite, and cockroach allergens, and polyclonal antibodies for Alternaria and dog antigens. The relationship between the antigen levels and home characteristics was investigated through a generalized multiple regression model. More than half of the homes experienced mold/water damage. Cats and dogs were present in 19.7% and 31.1% of homes, respectively. More than 90% of homes had either carpet or area rug covering their floors. Among 777 homes, 87–92% of homes had measurable amount of Alternaria, cat, and dog allergen/antigen in house dust, whereas only 38% and 14% of homes had measurable levels of house dust mite and cockroach, respectively. Alternaria antigen level in house dust was not associated with visual mold/water damage, which was suspected to be one of the sources for this antigen in homes. Instead, the antigen level was high in samples taken in fall and in homes having dogs implicating that Alternaria antigen appears to be transported from outdoors to indoors. A high level was also measured in homes using a dehumidifier (these homes have experienced excessive humidity) and in-home venting of clothes dryer, which might be associated with microclimate affecting mold growth and spore release. The allergen/antigen level (both concentration and loading) of cat, dog and cockroach was significantly associated with the number of cats and dogs, or the appearance of cockroaches, respectively. High level of house dust mite allergen was measured in bedrooms and in homes using dehumidifier and no central forced air heating system. Having indoor plants was shown to reduce allergen levels. Carpeted floor was found to hold larger amount of antigens than non-carpeted floor. Antigen loading demonstrated more consistent and larger numbers of associations with home characteristics compared to antigen concentration. This study encompassed a wide range of home characteristics and various antigen types. Our findings provide information on home characteristics that can be used for allergen avoidance and in planning future exposure assessment studies.